Hubungan Antara Kebisingan Dan Beban Kerja Dengan Stres Kerja Pada Pekerja Unit Perbaikan Di Pt. Kai Daop VI Yogyakarta Dipo Solo Balapan - Purnomo, Joko, H. Heru Subaris K, SKM., M.Kes, Dr. Suwaji, M.Kes (2016)
There are factors that affect the working environment such as physical factors, and the effect on health and safety in the workplace. The work environment is one of the main sources of potential occupational health hazards. One of the factors in the work environment is noise. Noise can have an impact, one of which can cause stress to a person exposed to noise. The purpose of this study was to determine the relationship between noise, age, length of employment, length of employment, and workload with work stress on workers' Service section VI DAOP PT KAI Yogyakarta DIPO Solo Racing. The sampling technique was purposive sampling method and using predetermined criteria to obtain a sample of 48 respondents. Instruments in this study was the measurement of the noise level by using a sound level meter and questionnaires noise, the stress of work, duration of work, tenure, and workload. Data analysis was performed using univariate and bivariate using Pearson's chi-square. The results showed a significant relationship between noise with work stress ((2 = 9.872; (= 0.002), age and job stress ((2 = 7.378; (= 0.002), length of employment with job stress ((2 = 16.061; ( = 0.000), duration of employment with job stress ((2 = 13.428; (= 0.000), and workload with job stress ((2 = 16.092; (= 0.000). Suggestions for the company is the quality control of the work to the employee by way of guidance periodically, giving insenftif, refreshing, and outbound order to reduce work stress.